Social Factors of Contractor Selection on Freelance Online Marketplace: Study of Contests Using “Big Data” - Strebkov, Denis; Shevchuk, Andrey; Lukina, Anastasia; Melianova Ekaterina; Tyulupo Alexey (Journal of Economic Sociology, 2019)
E-markets are online trading platforms designed to improve efficiency of interactions between sellers and buyers of goods and services. E-markets have become a fundamental organizational innovation in the information era. One example is freelance online marketplaces (online labor markets) that allow self-employed professionals (freelancers) and their clients to quickly and cost-effectively find each other anywhere in the world. Online labor markets substantially change the employment landscape and labor relations, actualizing the task of exploring contractual practices and mechanisms introduced by them. Similar to other websites, online labor markets record huge amounts of diverse information about the users and their actions. Utilizing such “big data,” we conducted research using factors that enable freelancers to win employment contests. The contest is one of the most popular mechanisms of freelancer selection, implying an open competition between all the candidates who perform the task set up by the competition organizer who finally determines a winner and pays a remuneration. The study uses open data on contests held from November 2009 to November 2018 on the largest Russianlanguage online marketplace. Data were collected automatically using a web scraping technique. The final sample consists of 6,169 contests, in which 335,613 freelancers took part, and the number of unique participants was 45,174 persons. The study results indicate the absence of persistent discrimination on the basis of socio-demographic characteristics. The results also revealed the important role of formalized reputation (embodied in ratings and reviews) and communication between the freelancer and the employer (in the form of mutual comments) that increase the chances of a freelancer winning a contest. The paper also discusses methodological issues that arise when working with “big data.” In general, this study of contests on freelance online marketplaces leads to the understanding of the role of social factors in the functioning of the new electronic economy based on “big data” generated by this economy.